Effects of Sumsu (Bufonis venenum) Pharmacopuncture Treatment on Depression in Mice - Min-ji Choi; Ka-na Kim; Jae-Eun Lee; Jin-Woo Suh; Sung- Chul Kim; Ki Rok Kwon; Seung-Hun Cho (Korean Pharmacopuncture Institute, 2014)
Objectives:The main objective of this study was to evaluate the anti-depressant effects of pharmacopuncture using sumsu (Bufonis venenum). Methods:Animals were divided into three groups (control, sham, and experimental), with eight mice per group. The sham and the experimental groups were exposed to 2 hours of immobilization stress daily for 14 days. They were also injected with normal saline (sham) or subjected to pharmacopuncture with sumsu at the acupoints HT7, SP6, and GV20 (experimental). The depression or anxiety-like behaviors of the mice in each group were evaluated 1 day after treatment. Results:There was no difference in locomotor activity between the groups during the open-field test; i.e., all groups had normal motor function. However, the open-field and the forced-swimming tests revealed that depression and anxiety-like behaviors were decreased significantly in the group treated with sumsu pharmacopuncture. Conclusion:Sumsu pharmacopuncture attenuated depressive or anxiety-like behavior in mice stressed with chronic immobilization. These results suggest that sumsu pharmacopuncture has therapeutic potential for treating neuropsychiatric disorders such as anxiety or depression disorder.